Graph Embedding for Pattern Recognition - Foggia, Pasquale; Vento, Mario (Recognizing Patterns in Signals, Speech, Images and Videos, 2010)
This is the report of the first contest on Graph Embedding for Pattern Recognition, hosted at the ICPR2010 conference in Istanbul. The aim is to define an effective algorithm to represent graph-based structures in terms of vector spaces, to enable the use of the methodologies and tools developed in the statistical Pattern Recognition field. For this contest, a large dataset of graphs derived from three available image databases has been constructed, and a quantitative performance measure has been defined. Using this measure, the algorithms submitted by the contest participants have been experimentally evaluated.